The Impact Mechanism of Entrepreneurial Team Expertise Heterogeneity on Entrepreneurial Decision - Ye, Suyang; Xiao, Yunchun; Yang, Bin; Zhang, Dong (Frontiers in Psychology, 2021)
Under the background of economic globalization and industrial revolution, team entrepreneurship has drawn increased attention. Team entrepreneurship is considered to be advantageous in its capability of integrating more abundant resources and of sharing knowledge, information, and complementary skills among members of the entrepreneurial team, enabling entrepreneurial enterprises to successfully adapt to the highly uncertain entrepreneurial environment. In recent years, the relationship between the heterogeneity of the entrepreneurial team and its decision-making quality has attracted much attention in the management research field. However, the research results on such topic are quite inconsistent. Based on the information processing theory, the greater the market uncertainty the entrepreneurial team faces, the stronger information integration ability a team will be required to possess. This paper investigates the mechanism and boundary conditions of the impact of entrepreneurial team’s expertise heterogeneity on entrepreneurial decision-making. It points out that team knowledge integration and team reflexivity have significant impacts on the relationship between entrepreneurial team expertise heterogeneity and entrepreneurial decision-making. This study adopts the multi-source design approach and collects data from 419 academic entrepreneurial teams in the University Science and Technology Park in Zhejiang Province. Hierarchical regression and bootstrapping methods are also employed for data analysis. The results show that team knowledge integration mediates the relationship between entrepreneurial team expertise heterogeneity and entrepreneurial decision-making, while team reflexivity moderates the relationship between entrepreneurial team expertise heterogeneity and team knowledge integration. In the final part, the practical implications for entrepreneurial team are discussed.